MIRACLE AND ITS SACRED SPACE IN THE MEDIEVAL VISUAL CULTURE OF PRILEP: THE CULT OF WONDERWORKING VIRGIN MARY OF THE MONASTERY OF TRESKAVEC (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2022)
This paper examines the role of miracles and wonderworking in the formation of sacred space within the medieval visual culture of Prilep. Particular attention is devoted to the cult of the wonderworking Virgin Mary at the Monastery of Treskavec, analyzed as a focal point of devotional practice and symbolic meaning. The study explores how narratives of miraculous intervention contributed to the construction of visual culture both within the interior of the church and across the broader sacred landscape. By situating miracle-working within its theological, liturgical, and spatial contexts, the paper demonstrates how visual representations, ritual practices, and topographical markers interacted in shaping a coherent sacred environment.
Keywords: miracle; sacred place; visual culture; wonderworking; Virgin Marry; Monastery of Treskavec